Distance-Regular Graphs - Van Dam, Edwin R.; Koolen, Jack H.; Tanaka, Hajime (The Electronic journal of combinatorics, 2016)
This is a survey of distance-regular graphs. We present an introduction to distance-regular graphs for the reader who is unfamiliar with the subject, and then give an overview of some developments in the area of distance-regular graphs since the monograph 'BCN' [Brouwer, A.E., Cohen, A.M., Neumaier, A., Distance-Regular Graphs, Springer-Verlag, Berlin, 1989] was written.